1978
DOI: 10.1172/jci109184
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plasma Vasopressin in Impaired Water Excretion of Glucocorticoid Deficiency

Abstract: A B S T R A C T In the present study, the effect of selective glucocorticoid deficiency on renal water excretion was investigated in conscious, trained, adrenalectomized dogs. The animals were studied before and after a water load while on replacement therapy of desoxycorticosterone acetate, 5 mg/day, and dexamethasone, 0.8 mg/day (group I), and while off dexamethasone for 5-9 days (group II). Before the water load the weight, inulin space, cardiac output, blood pressure, glomerular filtration rate, renal bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1
3

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(36 citation statements)
references
References 35 publications
2
29
1
3
Order By: Relevance
“…In both humans and experimental animals, adrenal insufficiency has been associated with several alterations in renal function, including impairment of urinary diluting and concentrating capacity (1)(2)(3)(4)(5)(6)(7). Isolated glucocorticoid deficiency has also been associated with impaired urinary concentration (8,9).…”
mentioning
confidence: 99%
“…In both humans and experimental animals, adrenal insufficiency has been associated with several alterations in renal function, including impairment of urinary diluting and concentrating capacity (1)(2)(3)(4)(5)(6)(7). Isolated glucocorticoid deficiency has also been associated with impaired urinary concentration (8,9).…”
mentioning
confidence: 99%
“…Dingman et al (1958) suggested that the hypersecretion of AVP occured in glucocorticoid deficit secondary to hypopituitarism with subsequent hyponatremia and an impaired urinary dilution, and glucocorticoid restored these derangements to normal. Moreover, Boykin et al (1978) showed that plasma AVP was elevated in mineralcorticoid-replaced adrenalectomized dogs even in a situation of lowered plasma osmolality induced by an acute water load, and glucocorticoid administration normalized the AVP response to hemodilution associated with a rise in cardiac output and blood pressure, suggesting the participation of the hemodynamic reflex-mediated suppression of AVP release. In the present case, the removal of glucocorticoid markedly increased plasma AVP, despite that there was no evidence of cardiovascular collapse and dehydration.…”
Section: Discussionmentioning
confidence: 97%
“…Pero el mecanismo es distinto al aceptado para la deficiencia de mineralocorticoides, desde el momento que por la deficiencia de glucocorticoides per se no se genera hipovolemia ni balance negativo de sodio. (8) Es conocido el rol de la vasopresina en la generación de hiponatremia euvolémica, debido a insuficiencia suprarrenal o hipotiroidismo (9,10,11,12,13) Parece claro sin embargo, que existen factores independientes de la vasopresina que también están comprometidos en la excreción alterada del agua que cursa con la deficiencia de glucocorticoides. Así, mientras el componente vasopresina-dependiente puede ser observado en ratas adrenalectomizadas privadas de glucocorticoides por 24 horas, el efecto vasopresina independiente de la excreción de agua ocurre luego de 2 semanas de deficiencia de glucocorticoides, en ratas deficientes en vasopresina.…”
Section: Discussionunclassified